Frequency of dosage prescribing medication errors associated with manual prescriptions for very preterm infants. (25th July 2014) - Horri, J.; Cransac, A.; Quantin, C.; Abrahamowicz, M.; Ferdynus, C.; Sgro, C.; Robillard, P.‐Y.; Iacobelli, S.; Gouyon, J.‐B.
Summary What is known and objective The risk of dosage Prescription Medication Error (PME) among manually written prescriptions within 'mixed' prescribing system (computerized physician order entry (CPOE) + manual prescriptions) has not been previously assessed in neonatology. This study aimed to evaluate the rate of dosage PME related to manual prescriptions in the high‐risk population of very preterm infants (GA < 33 weeks) in a mixed prescription system. Methods The study was based on a retrospective review of a random sample of manual daily prescriptions in two neonatal intensive care units (NICU) A and B, located in different French University hospitals (Dijon and La Reunion island). Daily prescription was defined as the set of all drugs manually prescribed on a single day for one patient. Dosage error was defined as a deviation of at least ±10% from the weight‐appropriate recommended dose. Results and discussion The analyses were based on the assessment of 676 manually prescribed drugs from NICU A (58 different drugs from 93 newborns and 240 daily prescriptions) and 354 manually prescribed drugs from NICU B (73 different drugs from 131 newborns and 241 daily prescriptions). The dosage error rate per 100 manually prescribed drugs was similar in both NICU: 3·8% (95% CI: 2·5–5·6%) in NICU A and 3·1% (95% CI: 1·6–5·5%) in NICU B (P = 0·54). Among all the 37 identified dosage errors, the over‐dosing was almost as frequent as the under‐dosing (17 and 20 errors, respectively). Potentially severe dosage errors occurred in a total of seven drug prescriptions. None of the dosage PME was recorded in the corresponding medical files and information on clinical outcome was not sufficient to identify clinical conditions related to dosage PME. Overall, 46·8% of manually prescribed drugs were off label or unlicensed, with no significant differences between prescriptions with or without dosage error. The risk of a dosage PME increased significantly if the drug was included in the CPOE system but was manually prescribed (OR = 3·3; 95% CI: 1·6–7·0, P < 0·001). What is new and conclusion The presence of dosage PME in the manual prescriptions written within mixed prescription systems suggests that manual prescriptions should be totally avoided in neonatal units.